Altruism, social norms, and incentive contract design - Abernethy, Margaret A.; Bouwens, Jan; Hofmann, Christian; van Lent, Laurence (Review of Accounting Studies, 2023)
Abstract We study theoretically and empirically the relation between altruism and incentive contract design. Theoretically, we extend Fischer and Huddart (2008) to investigate how social norms reinforce managers’ altruistic preferences, thus affecting the optimal contract design related to incentive strength and performance measurement. Empirically, we draw on the notion of an organization’s work climate to capture managers’ altruistic preferences. Using data collected from a sample of 557 managers, we find that in a work climate where managers are mostly out for themselves, firms have lower pay-for-performance sensitivity and place a greater weight on aggregate performance measures. In addition, respondents report that they engage more in undesirable actions that are unproductive and costly to firm owners. In contrast, in a work climate where managers care about others (including peers in their organizational unit), firms place lower weights on aggregate performance measures. At the same time, respondents report that they supply more effort and engage less in undesirable actions.